A flexible conductive hydrogel with electrochemiluminescence properties and its application

By preparing flexible conductive hydrogels with electrochemiluminescence characteristics, the problems of poor stability of zinc protoporphyrin and difficulty in detecting amine substances are solved, and high sensitivity and low cost detection of amine substances are achieved, which improves the environment and health Protection efficiency.

CN115873267BActive Publication Date: 2024-12-13NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211524268.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2024-12-13
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

Zinc protoporphyrin has poor ECL stability in electrochemiluminescence, and the prior art is difficult to detect amines quickly and sensitively, resulting in threats in environmental and health protection.

Method used

By preparing a flexible conductive hydrogel with electrochemiluminescence characteristics, GP hydrogel is formed using guanosine, boric acid, hydroxide and agarose, and GPP conductive hydrogel is obtained by polymerization of aniline, combined with microfluidic technology Construct ECL imaging conductive devices for detection of amines.

Benefits of technology

It realizes the high sensitivity, stability and low cost preparation of GPP conductive hydrogels, and can quickly and accurately detect triproamine, triethylamine, cysteine ​​and 2-(dibutylamino)ethanol, with good linear relationships. and repeatability, improving detection efficiency and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115873267B_ABST
    Figure CN115873267B_ABST
Patent Text Reader

Abstract

The present invention discloses a flexible conductive hydrogel with electrochemiluminescence characteristics and its application. The flexible conductive hydrogel is prepared by adding hydroxide to guanosine and boric acid solution to obtain guanosine-tetrad; then adding agarose and zinc protoporphyrin to obtain GP hydrogel; then transferring the GP hydrogel to an aniline solution, and then adding hydrogen peroxide to prepare. The flexible conductive hydrogel solves the problem of poor and unstable electrochemiluminescence signals of pure zinc protoporphyrin. Detection of amine substances is of great significance to the protection of health and environment. The amine substances detected in the present invention have an inhibitory effect on the electrochemiluminescence signal of the flexible conductive hydrogel, and the logarithm of the concentration of the amine substances is linearly related to the electrochemiluminescence signal of the flexible conductive hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of physical and chemical analysis, and in particular relates to a flexible conductive hydrogel with electrochemiluminescence characteristics and an application thereof. Background Art

[0002] In recent decades, electrochemiluminescence (ECL) analysis has attracted much attention due to its advantages such as high sensitivity, low background, wide dynamic range, easy control and simple equipment. In ECL detection, seeking excellent ECL luminophores is the key to ensuring high efficiency of ECL. Zinc protoporphyrin (ZnPPIX), as an excellent ECL luminophore, not only has a macrocyclic structure of a π-conjugated system that can provide good π-π conversion and electron transfer, but can also be used as an efficient oxygen reduction reaction (ORR) catalyst. The unique ECL kinetics of its cathode is to increase the activation activity of molecular oxygen by means of its electrocatalytic reduction, and then produce ECL emission. However, since the ECL intermediates of pure zinc protoporphyrin monomers are prone to aggregation and photobleaching, they lead to poor conductivity and ECL stability, thus limiting their further application in electrochemiluminescence sensing. Therefore, protective assembly with stable structure and high electron transfer rate is particularly important.

[0003] Conductive hydrogel is a conductive composite material among many types of hydrogels, usually composed of hydrogel and conductive materials. It has many advantages such as good biocompatibility, variable structure, easy processing, high mechanical flexibility, excellent electrical and optical properties, high oxidation activity, etc. In addition, the network structure of hydrogel facilitates the diffusion of electrons, ions, and small molecules. The conductive polymer chain can provide a continuous material transport pathway. Combining the two can construct a sensor with high sensitivity, wide linear range and fast response time.

[0004] Many amines and their derivatives are highly toxic compounds and have been shown to be carcinogenic. The production and use of these compounds may lead to their release into the environment through various wastes, which can cause serious environmental problems and endanger human health. For example, triethylamine is not only irritating to the respiratory tract, causing chemical burns and pulmonary edema, but also may cause an explosive crisis when mixed with air and exposed to a fire source. Therefore, detecting their content in samples is of great significance for protecting health and the environment. From the perspective of health and environmental protection, developing a simple, fast and sensitive sensor to detect them has become an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies of the prior art and provide a flexible conductive hydrogel with electrochemiluminescence properties and its application, which not only solves the problem of poor ECL stability of zinc protoporphyrin, but also can be used for rapid detection of four amine substances and has good detection performance.

[0006] The object of the present invention is achieved through the following technical solution: A flexible conductive hydrogel with electrochemiluminescence characteristics is obtained by the following preparation method:

[0007] (1) First, guanosine and 45-55 mM boric acid solution are weighed and shaken in a test tube until the two are evenly mixed, wherein the molar ratio of boric acid to guanosine is (1-4):(1-4); then, the test tube is placed in a water bath at 90-100° C. for heat treatment until the solution becomes clear; then, hydroxide is added and heat treatment is continued to obtain guanosine-quadruplex, wherein the molar ratio of boric acid to hydroxide is 1:1; then, agarose is added and heating is continued until the agarose is completely dissolved, so that the final concentration of agarose is 7-24 mM; then, the water bath temperature is lowered to 60-80° C., zinc protoporphyrin is added to a final concentration of 0.1-5.5 mM, mixed, and continued to be heated in a water bath until the solution is a purple-red transparent solution; finally, aging is performed at room temperature to obtain GP hydrogel;

[0008] (2) transferring the GP hydrogel obtained in step (1) to an aniline solution and allowing it to stand, wherein the molar ratio of aniline to hydroxide is 1:1; adjusting the pH to 3, then adding hydrogen peroxide and allowing it to stand to initiate aniline polymerization, wherein the molar ratio of hydrogen peroxide to aniline is 1:1, centrifuging, and discarding the upper layer solution to obtain a lower layer of GPP conductive hydrogel, i.e., a flexible conductive hydrogel with electrochemiluminescent properties.

[0009] Furthermore, the hydroxide is potassium hydroxide, lithium hydroxide or sodium hydroxide.

[0010] Furthermore, the hydroxide is potassium hydroxide.

[0011] Furthermore, the concentration ratio of the hydroxide:guanosine is 1:2.

[0012] Furthermore, the concentration of zinc protoporphyrin is 1.5 mM.

[0013] Furthermore, the aniline polymerization time is 0 to 4 hours.

[0014] Furthermore, the aniline polymerization time is 2 hours.

[0015] Furthermore, the GPP conductive hydrogel has a porous structure.

[0016] The above-mentioned flexible conductive hydrogel with electrochemiluminescence properties is used in the preparation of electrodes for detecting amine substances.

[0017] Furthermore, the electrode is obtained by the following preparation method:

[0018] (1) Grind the electrode until the surface is smooth;

[0019] (2) The electrode polished in step (1) is ultrasonically treated in anhydrous ethanol and deionized water, and then blown dry with nitrogen;

[0020] (3) Dropping the flexible conductive hydrogel on the surface of the electrode and leaving it to dry at room temperature to form a thin film, thereby obtaining an electrode capable of detecting amine substances.

[0021] The beneficial effects of the present invention are as follows:

[0022] (1) The preparation method of GPP conductive hydrogel is simple, rapid and low-cost;

[0023] (2) The highly porous structure of GPP hydrogel facilitates the free diffusion of the analyte, thereby improving the detection sensitivity.

[0024] (3) Amine substances including tripropylamine, triethylamine, cysteine ​​and 2-(dibutylamino)ethanol inhibited the ECL signal of GPP conductive hydrogel with good linearity, high sensitivity, and satisfactory stability and repeatability.

[0025] (4) GPP conductive hydrogel can be combined with microfluidic technology to construct a flexible ECL imaging conductive device, so as to visually observe the ECL signal inhibitory effect of tripropylamine on GPP conductive hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the process of preparing electrode surface film; wherein, Figure (a) is the synthesis process of GP hydrogel, and Figure (b) is the synthesis of GPP conductive hydrogel and the process of preparing electrode surface film;

[0027] Figure 2 Fourier transform infrared spectra of boric acid, guanosine-quadruplex, GP hydrogel, and GPP conductive hydrogel;

[0028] Figure 3 UV and fluorescence spectra of zinc protoporphyrin, guanosine-tetramer, GP hydrogel and GPP conductive hydrogel;

[0029] Figure 4 The scanning electron microscope images of GPP conductive hydrogel; wherein, Figure (a) is a scanning electron microscope of GPP conductive hydrogel ×2K magnification, and Figure (b) is a scanning electron microscope of GPP conductive hydrogel ×20K magnification;

[0030] Figure 5The normalized ECL-voltage diagrams of the GCE / ZnPPIX electrode and the GCE / GPP electrode under nitrogen, air and oxygen conditions, respectively; wherein, Figure (a) is the normalized ECL-voltage diagram of the GCE / ZnPPIX electrode under nitrogen, air and oxygen conditions, and Figure (b) is the normalized ECL-voltage diagram of the GCE / GPP electrode under nitrogen, air and oxygen conditions;

[0031] Figure 6 The normalized ECL-time diagrams of the GCE / ZnPPIX electrode and the GCE / GPP electrode under nitrogen, air and oxygen conditions, respectively; wherein, Figure (a) is the normalized ECL-time diagram of the GCE / ZnPPIX electrode under nitrogen, air and oxygen conditions, and Figure (b) is the normalized ECL-time diagram of the GCE / GPP electrode under nitrogen, air and oxygen conditions;

[0032] Figure 7 To obtain the optimal ECL signal conditions of the GCE / GPP electrode; wherein, Figure (a) is the concentration of zinc protoporphyrin, Figure (b) is the polymerization time of aniline, Figure (c) is the ratio of potassium hydroxide to guanosine, and Figure (d) is a comparison of different hydroxides as the synthetic GPP conductive hydrogel;

[0033] Figure 8 The linear equation curves obtained by the GCE / GPP electrode for quantitatively detecting tripropylamine, triethylamine, cysteine ​​and 2-(dibutylamino)ethanol, respectively; wherein, Figure (a) is a linear equation curve obtained by the GCE / GPP electrode for quantitatively detecting tripropylamine, Figure (b) is a linear equation curve obtained by the GCE / GPP electrode for quantitatively detecting triethylamine, Figure (c) is a linear equation curve obtained by the GCE / GPP electrode for quantitatively detecting cysteine, and Figure (d) is a linear equation curve obtained by the GCE / GPP electrode for quantitatively detecting 2-(dibutylamino)ethanol;

[0034] Fig. 9 Schematic diagram of GPP hydrogel microfluidic chip;

[0035] Fig.10 The construction of the ECL imaging microfluidic platform based on GPP hydrogel, where WE is the working electrode, CE is the counter electrode, and RE is the reference electrode;

[0036] Fig.11 These are images obtained based on GPP conductive hydrogel combined with microfluidic technology; Figure (a) is an ECL luminescence image, and Figure (b) is an ECL image for qualitative detection of tripropylamine;

[0037] Among them, PDMS1, cover glass 2. DETAILED DESCRIPTION

[0038] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of devices and methods consistent with some aspects of the present invention as detailed in the appended claims.

[0039] The present invention is described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the features of the following embodiments and implementations can be combined with each other.

[0040] The flexible conductive hydrogel with electrochemiluminescence characteristics of the present invention is obtained by the following preparation method:

[0041] (1) First, guanosine and 45-55 mM boric acid solution are weighed and shaken in a test tube until the two are evenly mixed, wherein the molar ratio of boric acid to guanosine is (1-4):(1-4); then, the test tube is placed in a water bath at 90-100° C. for heat treatment until the solution becomes clear; then, hydroxide is added and heat treatment is continued to obtain guanosine-quadruplex, wherein the molar ratio of boric acid to hydroxide is 1:1; then, agarose is added and heating is continued until the agarose is completely dissolved, so that the final concentration of agarose is 7-24 mM; then, the water bath temperature is lowered to 60-80° C., zinc protoporphyrin is added to a final concentration of 0.1-5.5 mM, mixed, and continued to be heated in a water bath until the solution is a purple-red transparent solution; finally, aging is performed at room temperature to obtain GP hydrogel;

[0042] (2) transferring all the GP hydrogel obtained in step (1) into an aniline solution and letting it stand, wherein the molar ratio of aniline to hydroxide is 1:1; adjusting the pH to 3, then adding hydrogen peroxide and letting it stand to initiate aniline polymerization, wherein the molar ratio of hydrogen peroxide to aniline is 1:1, centrifuging, and discarding the upper layer solution to obtain a lower layer of GPP conductive hydrogel, i.e., a flexible conductive hydrogel with electrochemiluminescent properties.

[0043] In some embodiments, the hydroxide is potassium hydroxide, lithium hydroxide or sodium hydroxide; preferably potassium hydroxide;

[0044] In some embodiments, the molar ratio of hydroxide to guanosine is preferably 1:2;

[0045] In some embodiments, the concentration of zinc protoporphyrin is preferably 1.5 mM;

[0046] In some embodiments, the aniline polymerization time is 0 to 4 hours, preferably 2 hours.

[0047] The present invention is further described in detail below in conjunction with specific embodiments and accompanying drawings:

[0048] Embodiment 1:

[0049] (1) First, guanosine and 45 mM boric acid solution are weighed and shaken in a test tube until the two are evenly mixed, and the molar ratio of boric acid to guanosine is 4:1; then the test tube is placed in a 90°C water bath for heat treatment until the solution becomes clear; then lithium hydroxide is added and heat treatment is continued to obtain guanosine-tetramer, and the molar ratio of boric acid to hydroxide is 1:1; then agarose is added and continued to be heated until the agarose is completely dissolved, so that the final concentration of agarose is 7 mM; then the water bath temperature is lowered to 60°C, zinc protoporphyrin is added to a final concentration of 0.1 mM, mixed, and continued to be heated in a water bath until the solution is a purple-red transparent solution; finally, aged at room temperature for 2 hours to obtain GP hydrogel;

[0050] (2) The GP hydrogel obtained in step (1) is transferred to an aniline solution and allowed to stand, wherein the molar ratio of aniline to hydroxide is 1:1; the pH is adjusted to 3, and then hydrogen peroxide is added and allowed to stand to initiate aniline polymerization, wherein the molar ratio of hydrogen peroxide to aniline is 1:1, and the aniline polymerization is 0 hours; finally, the GP hydrogel is transferred to a centrifuge for centrifugation (9000 r / min, 30 minutes), and the upper layer solution is poured off to obtain the GPP conductive hydrogel in the lower layer, i.e., a flexible conductive hydrogel with electrochemiluminescence properties.

[0051] Embodiment 2:

[0052] (1) First, guanosine and 55 mM boric acid solution were weighed and shaken in a test tube until the two were evenly mixed, and the molar ratio of boric acid to guanosine was 1:4; then the test tube was placed in a 100°C water bath for heat treatment until the solution became clear; then sodium hydroxide was added and continued to be heat treated to obtain guanosine-quadruplex, and the molar ratio of boric acid to hydroxide was 1:1; then agarose was added and continued to be heated until the agarose was completely dissolved, so that the final concentration of agarose was 24 mM; then the water bath temperature was lowered to 80°C and zinc protoporphyrin was added to a final concentration of 5.5 mM, mixed, and continued to be heated in a water bath until the solution was a purple-red transparent solution; finally, aged at room temperature for 2 hours to obtain GP hydrogel;

[0053] (2) The GP hydrogel obtained in step (1) is transferred to an aniline solution and allowed to stand, wherein the molar ratio of aniline to hydroxide is 1:1; the pH is adjusted to 3, and then hydrogen peroxide is added and allowed to stand to initiate aniline polymerization, wherein the molar ratio of hydrogen peroxide to aniline is 1:1, and the aniline polymerization is carried out for 4 hours. Finally, the GP hydrogel is transferred to a centrifuge for centrifugation (9000 r / min, 30 minutes), and the upper layer solution is poured off to obtain the GPP conductive hydrogel in the lower layer, i.e., a flexible conductive hydrogel with electrochemiluminescence properties.

[0054] Embodiment 3:

[0055] (1) First, guanosine and 50 mM boric acid solution are weighed and shaken in a test tube until the two are evenly mixed, and the molar ratio of boric acid to guanosine is 1:2; then the test tube is placed in a 95°C water bath for heat treatment until the solution becomes clear; then potassium hydroxide is added and heat treatment is continued to obtain guanosine-quadruplex, and the molar ratio of boric acid to hydroxide is 1:1; then agarose is added and continued to be heated until the agarose is completely dissolved, so that the final concentration of agarose is 16 mM; then the water bath temperature is lowered to 80°C, zinc protoporphyrin is added to a final concentration of 1.5 mM, mixed, and continued to be heated in a water bath until the solution is a purple-red transparent solution; finally, aged at room temperature for 2 hours to obtain GP hydrogel;

[0056] (2) The GP hydrogel obtained in step (1) is transferred to an aniline solution and allowed to stand; the pH is adjusted to 3, and then 50 mM hydrogen peroxide is added and allowed to stand to initiate aniline polymerization. The aniline polymerization is carried out for 2 hours, and finally the solution is transferred to a centrifuge for centrifugation (9000 r / min, 30 minutes), and the upper layer of the solution is poured off to obtain the GPP conductive hydrogel in the lower layer, i.e., a flexible conductive hydrogel with electrochemiluminescence properties.

[0057] Schematic diagram of the synthesis process of GP hydrogel Figure 1 As shown in Figure (a), the schematic diagram of GPP conductive hydrogel is as follows Figure 1 As shown in Figure (b).

[0058] Boric acid, guanosine-quadruplex, GP hydrogel and GPP conductive hydrogel were characterized by Fourier transform infrared spectroscopy, such as Figure 2 As shown, the v of boric acid B-O At 1430cm -1 There is an absorption band; while the v of boric acid O-H =3196cm -1 and δ B-OH =1195cm -1 After the gel is formed, it disappears. When the amide participates in hydrogen bonding and potassium ions (K + ) complex, the free guanosine molecule is at 1721cm -1 The amide vibration at 1645 cm-1 will move to the direction of low wave velocity. Therefore, it can be seen that the amide vibration of GP hydrogel and GPP hydrogel appears at 1645 cm-1, -1 and 1681cm -1 This indicates that guanosine participates in the formation of hydrogen bonds and K + Ion complexation. At 1051cm -1 v B-OC The vibrations indicate the formation of a boronate ester, which implies the synthesis of a guanosine-quadruplex.

[0059] Zinc protoporphyrin, guanosine-quadruplex, GP hydrogel and GPP conductive hydrogel were dissolved in acetonitrile, and the UV absorption spectra and fluorescence spectra of various solutions were measured. Figure 3 As shown, zinc protoporphyrin has an obvious absorption peak (B band) at 414nm and Q bands at 543nm and 582nm. Guanosine-tetramer itself has almost no ultraviolet absorption peak. Compared with zinc protoporphyrin, the absorption peak of GP hydrogel did not shift at all, but the absorbance increased significantly. The reasonable explanation is that the structure of GP hydrogel disperses the easily aggregated porphyrin, which leads to an increase in absorbance. The maximum absorption wavelength of GPP hydrogel red-shifted from 414nm to 415nm and the absorbance decreased significantly, which is due to the influence of polyaniline. The corresponding fluorescence spectrum was measured using the maximum absorption wavelength measured by ultraviolet absorption light as the excitation wavelength (λem=414nm). Compared with zinc protoporphyrin and guanosine-tetramer, the fluorescence intensity of GP hydrogel increased significantly. The fluorescence intensity of GPP hydrogel is only 48% of that of zinc protoporphyrin. The above results are consistent with the results of ultraviolet absorption spectrum. The above shows the successful synthesis of GP hydrogel and GPP hydrogel.

[0060] The GPP hydrogel was photographed under a scanning electron microscope. Figure 4 shown. Figure 4 Figure (a) is a scanning electron microscope image of the GPP conductive hydrogel at ×2K magnification, which clearly shows the rough and uneven structure of the GPP conductive hydrogel surface; Figure 4 Figure (b) is a scanning electron microscope image of the GPP conductive hydrogel at ×20K magnification, which shows that the basic gel molecule of the GPP hydrogel is a fibrous structure with a fiber diameter of about 0.9 μm.

[0061] Example 4: Preparation of GCE / GPP Electrode and GCE / ZnPPIX Electrode

[0062] The glassy carbon electrode (GCE) was polished with 0.05 μm alumina suspension until the surface was smooth; the electrode was ultrasonically treated in anhydrous ethanol and deionized water successively, and then blown dry with nitrogen; 25 μL of GPP conductive hydrogel was dropped on the pretreated GCE surface and allowed to dry at room temperature to form a thin film, which was recorded as a GCE / GPP electrode.

[0063] The GCE / ZnPPIX electrode was prepared using the same steps as above, except that 25 μL of GPP conductive hydrogel was replaced with 25 uL of 1.5 mM zinc protoporphyrin solution.

[0064] The construction process of GCE / GPP electrode is as follows Figure 1 As shown in Figure (b).

[0065] Example 5: ECL signal detection

[0066] GCE / ZnPPIX electrode and GCE / GPP electrode were used as working electrodes, platinum wire electrode was used as auxiliary electrode, and Ag / AgCl (saturated potassium chloride) electrode was used as reference electrode. The parameters of the electrochemiluminescence analysis system were set as follows: the amplification level was 3, a potential of -2.1 to 0V was applied to the working electrode, the photomultiplier tube bias voltage was -1000V, and the scanning rate was 0.1V / s. The ECL buffer used in the experiment was an oxygen or nitrogen saturated acetonitrile solution containing 0.1M tetrabutylammonium perchlorate. The oxygen saturated solution or nitrogen saturated solution was prepared by respectively flushing high-purity O 2 or N 2 The ECL voltage and ECL time diagrams of the GCE / ZnPPIX electrode and the GCE / GPP electrode were recorded under nitrogen, air, and oxygen conditions at room temperature.

[0067] like Figure 5 As shown in Figure 2, the normalized ECL-voltage diagrams of the GCE / ZnPPIX electrode and the GCE / GPP electrode under nitrogen, air, and oxygen conditions, respectively. The ECL signals of both the GCE / ZnPPIX electrode and the GCE / GPP electrode in oxygen are the strongest, and under the same conditions, the ECL signal of the GCE / GPP electrode is stronger than that of the GCE / ZnPPIX electrode.

[0068] like Figure 6 As shown, the normalized ECL-time graphs of the GCE / ZnPPIX electrode and the GCE / GPP electrode under nitrogen, air, and oxygen conditions, respectively. The ECL signal of the GCE / ZnPPIX electrode is unstable under the three conditions, while the ECL signal of the GCE / GPP electrode is stable under the three conditions.

[0069] like Figure 7 As shown in Figure 1, (a) shows that the ECL signal of the GCE / GPP electrode is best at a concentration of 1.5 mM zinc protoporphyrin, (b) shows that the ECL signal of the GCE / GPP electrode is best at a polymerization time of 2 hours for aniline, (c) shows that the ECL signal of the GCE / GPP electrode is best at a potassium hydroxide: guanosine concentration of 1:2, and (d) shows that the ECL signal is best at a magnesium ion (Mg 2+ ) is the best, followed by calcium ions (Ca 2+ ), potassium ion (K + ) and sodium ions (Na + ), and finally lithium ion (Li + ), but due to Mg 2+ and Ca 2+ These two substances have low solubility and cannot form conductive hydrogels, so the ECL signal of the GCE / GPP electrode is in the potassium (K+ ) ions achieve the best.

[0070] Example 6: Application of GCE / GPP electrodes in the detection of four amine substances

[0071] (1) The working surface of the glassy carbon electrode (GCE) was polished with a 0.05 μm alumina suspension to obtain a smooth mirror surface. The electrode was ultrasonically treated in anhydrous ethanol and deionized water, and then dried with nitrogen;

[0072] (2) 25 μL of GPP conductive hydrogel was dropped onto the pretreated GCE surface and allowed to dry at room temperature to form a thin film. The modified electrode was denoted as GCE / GPP.

[0073] (3) GCE / GPP was used as the working electrode, the platinum wire electrode was used as the auxiliary electrode, and the Ag / AgCl (saturated potassium chloride) electrode was used as the reference electrode;

[0074] (4) The parameters of the electrochemiluminescence analysis system were set as follows: the amplification level was 3, the potential of -2.1 to 0 V was applied to the working electrode, the photomultiplier tube bias voltage was -1000 V, and the scanning rate was 0.1 V / s;

[0075] (5) The ECL buffer used in the experiment was acetonitrile containing 0.1 M tetrabutylammonium perchlorate, after which high-purity oxygen was bubbled in for 30 minutes to prepare an oxygen-saturated ECL buffer;

[0076] (6) Different concentrations of tripropylamine, triethylamine, cysteine ​​and 2-(dibutylamino)ethanol were added to the oxygen-saturated ECL buffer, and the concentration gradient of the substances was 1 pM to 10 μM, and then the measurement was performed at room temperature.

[0077] Specific test results are as follows Figure 8 As shown:

[0078] like Figure 8 As shown in Figure (a), the ECL signal of the GCE / GPP electrode decreases with the increase of tripropylamine concentration, and the response maintains a good linear relationship in the six orders of magnitude concentration range of 1pM to 100nM. In this range, the concentration of tripropylamine can be quantitatively detected, and the linear equation is I ECL1 =-2512.865logC (三丙胺) +14386.090(Correlation coefficient R 1 2 =0.967), I ECL1 is the ECL signal of GCE / GPP electrode in tripropylamine solution with different concentrations, logC (三丙胺) is the logarithm of the concentration of tripropylamine.

[0079] like Figure 8As shown in Figure (b), the ECL signal of the GCE / GPP electrode decreases with the increase of triethylamine concentration, and the response maintains a good linear relationship in the six orders of magnitude concentration range of 1pM to 100nM. In this range, the triethylamine concentration can be quantitatively detected, and the linear equation is I ECL2 =-1164.743logC (三乙胺) +14236.714(Correlation coefficient R 1 2 =0.998), I ECL2 is the ECL signal of GCE / GPP electrode in triethylamine solution with different concentrations, logC (三乙胺) is the logarithm of the concentration of triethylamine.

[0080] like Figure 8 As shown in Figure (c), the ECL signal of the GCE / GPP electrode decreases with the increase of cysteine ​​concentration, and the response maintains a good linear relationship in the five orders of magnitude concentration range of 1pM to 10nM. In this range, the cysteine ​​concentration can be quantitatively detected, and the linear equation is I ECL3 =-3607.337logC (半胱氨酸) +17151.364(Correlation coefficient R 3 2 =0.994), I ECL3 is the ECL signal of GCE / GPP electrode in cysteine ​​solution with different concentrations, logC (半胱氨酸) is the logarithm of the cysteine ​​concentration.

[0081] like Figure 8 As shown in Figure (d), the ECL signal of the GCE / GPP electrode decreases with the increase of 2-(dibutylamino)ethanol concentration, and the response maintains a good linear relationship in the five orders of magnitude concentration range of 1pM to 10nM. In this range, the concentration of 2-(dibutylamino)ethanol can be quantitatively detected, and the linear equation is I ECL4 =-2121.368logC (2-(二丁氨基)乙醇) +10598.156(Correlation coefficient R 4 2 =0.997), I ECL4 is the ECL signal of GCE / GPP electrode in 2-(dibutylamino)ethanol solution with different concentrations, logC (2-(二丁氨基)乙醇) It is the logarithm of the concentration of 2-(dibutylamino)ethanol.

[0082] The linear equation obtained above is obtained through fitting, that is, after the software inputs the data points, it selects the linear fitting curve to obtain the linear equation; the correlation coefficient R 2 It is the relative deviation of each original data point from the fitting curve, and also indicates the credibility of the fitting curve.

[0083] Conclusion: Amine substances have an inhibitory effect on the luminescence of GPP conductive hydrogel, that is, when the concentration of amine substances is continuously increased, the luminescence of GPP conductive hydrogel gradually weakens until the luminescence of GPP conductive hydrogel is quenched.

[0084] Example 7: GPP conductive hydrogel microfluidic technology construction

[0085] Based on the conclusion of Example 6, the construction of GPP conductive hydrogel microfluidic technology can be used to qualitatively detect whether a substance contains amine substances. If the luminescence of GPP conductive hydrogel is weakened or quenched when a certain substance is added, the substance contains amine substances; otherwise, the substance does not contain amine substances.

[0086] A fully transparent microfluidic sensor device with a size of 30 mm × 15 mm × 10 mm was made using polydimethylsiloxane (PDMS). Fig. 9 As shown in the figure, the microfluidic sensor device is constructed by bonding two layers of PDMS 1 and a cover glass 2 through spark discharge activation. The 2mm diameter round hole in the upper PDMS layer is used to connect the reference electrode and the counter electrode, the 10mm×10mm square hole in the middle is used to place the working electrode, i.e., the GCE / GPP electrode, and the necessary electrolyte is stored in the 25mm×5mm PDMS groove in the lower layer to form a complete three-electrode system.

[0087] like Fig.10 As shown in the figure, the schematic diagram of the process of detecting tripropylamine by GPP conductive hydrogel microfluidic technology: GPP conductive hydrogel generates ECL signal under the action of electric field and is received by the photosensitive element through the cover glass. By combining the device with a fluorescent inverted microscope, the ECL image of the material was obtained by continuous exposure for 2 minutes under a 4× objective lens through NIS-Elements AR 5.20.00.

[0088] like Fig.11 As shown in Figure (a), it can be seen in the ECL image that the GPP conductive hydrogel has a luminescent phenomenon in the acetonitrile buffer solution, such as Fig.11 As shown in Figure (b), after adding 0.1M tripropylamine, the luminescence of GPP conductive hydrogel is quenched.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0090] The above embodiments are only used to illustrate the design ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly. The protection scope of the present invention is not limited to the above embodiments. Therefore, any equivalent changes or modifications made based on the principles and design ideas disclosed by the present invention are within the protection scope of the present invention.

[0091] Those skilled in the art will readily appreciate other embodiments of the present application after considering the description and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application. The description and examples are intended to be exemplary only.

[0092] It should be understood that the present application is not limited to the exact construction that has been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof.

Claims

1. Application of a flexible conductive hydrogel with electrochemiluminescence properties, characterized in that: The flexible conductive hydrogel with electrochemiluminescence characteristics is obtained by the following preparation method: (1) First, weigh guanosine and 45-55 mM boric acid solution and shake them in a test tube until the two are evenly mixed, wherein the molar ratio of boric acid to guanosine is (1-4):(1-4); then, place the test tube in a 90-100°C water bath for heat treatment until the solution becomes clear; then, add hydroxide and continue heat treatment to obtain guanosine-quadruplex, wherein the molar ratio of boric acid to hydroxide is 1:1; then, add agarose and continue heating until the agarose is completely dissolved, so that the final concentration of agarose is 7-24 mM; then, lower the water bath temperature to 60-80°C, add zinc protoporphyrin to a final concentration of 0.1-5.5 mM, mix well, and continue heating in a water bath until the solution is a purple-red transparent solution; finally, age at room temperature to obtain GP hydrogel; (2) transferring the GP hydrogel obtained in step (1) to an aniline solution and allowing it to stand, wherein the molar ratio of aniline to hydroxide is 1:1; adjusting the pH to 3, then adding hydrogen peroxide and allowing it to stand to initiate aniline polymerization, wherein the molar ratio of hydrogen peroxide to aniline is 1:1, centrifuging, and discarding the upper layer solution to obtain a GPP conductive hydrogel at the lower layer, i.e., a flexible conductive hydrogel with electrochemiluminescent properties; Application of the flexible conductive hydrogel with electrochemiluminescence properties in preparing an electrode capable of detecting amine substances; The hydroxide is potassium hydroxide, lithium hydroxide or sodium hydroxide.

2. The use according to claim 1, characterized in that: The hydroxide is potassium hydroxide.

3. The use according to claim 1, characterized in that: The molar ratio of the hydroxide to guanosine is 1:

2.

4. The use according to claim 1, characterized in that: The concentration of zinc protoporphyrin was 1.5 mM.

5. The use according to claim 1, characterized in that: The aniline polymerization time is 0 to 4 hours and is not 0.

6. The use according to claim 5, characterized in that: The aniline polymerization time is 2 hours.

7. The use according to claim 1, characterized in that: The GPP conductive hydrogel has a porous structure.

8. The use according to claim 1, characterized in that: The electrode is obtained by the following preparation method: (1) Grind the electrode until the surface is smooth; (2) The electrode polished in step (1) is ultrasonically treated in anhydrous ethanol and deionized water, and then blown dry with nitrogen; (3) Drop the flexible conductive hydrogel on the electrode surface and let it dry at room temperature to form a thin film, thereby obtaining an electrode capable of detecting amine substances.